Human trafficking: vulnerability, impact, and action - Shamsudeen, Sheeba (Victimology, 2022)
A modern-day slavery and a crime against humanity, thousands of cases of human trafficking are reported across the world each year. Being a billion-dollar criminal industry, the illegal exploitation of men, women, and children for sexual exploitation, forced labour, and other rackets contribute to this international organized crime network. Understanding the methods employed by traffickers using force, coercion, or fraud helps identify the risk factors and vulnerabilities of victims at high risk for trafficking. These red flags shed light on the liabilities of trafficked men, women, and children and help devise prevention strategies to curb this form of crime. Major theories from a psychosocial perspective are discussed, which supports formulating a better understanding of human trafficking. The impact of trafficking is seen on various aspects of an individual’s life, especially on their physical and mental health. These social and economic impacts help comprehend the burden experienced by these victims. Psychological therapies designed to deal with the aftermath of trauma due to trafficking can aid practitioners in delivering tailored interventions. Forensic and psychiatric protocols to evaluate, identify, and support victims of human trafficking can assist in medicolegal proceedings.